A multi-objective optimization framework for seismic resilience enhancement of typical existing RC buildings. (15th July 2022) - Omidian, Pedram; Khaji, Naser
Abstract: Structural retrofitting is a common approach to increase the resilience of the existing buildings (e.g., office buildings) in the industrial (e.g., refinery) sites against earthquakes. In this study, a typical RC structure that used as operational office building is considered, for which a multi-objective framework is proposed to select the retrofit patterns that are optimized for seismic resilience index and cost of retrofit of these buildings. For this purpose, three different jacketing materials (i.e., Steel, CFRP and GFRP) with four various thicknesses for each one (1.2, 2.4, 3.6 and 4.8 mm for Steel, and 1 to 4 plies for CFRP and GFRP) are chosen to retrofit these buildings. In addition, six different plans are considered for the retrofit designs. Besides, three seismic intensity levels from low to severe seismic intensities with different distances ranging from near-to far-field are taken into account to determine the sensitivity of responses. For each scenario, the fragility values for calculating the seismic resilience index, and the cost of retrofit are obtained, and then the optimal set of solutions is calculated by applying the well-established non-dominated sorting genetic algorithm II. The results show that the structural retrofitting not only reduces the sensitivity of the structural response to different seismic inputs in a limited range, but also improves the performance of the structure in terms of resilience index especially at higher intensities. The proposed framework provides a method for decision makers to choose optimal retrofit strategies that minimize the corresponding costs, while achieving a predesigned resilience's level for an infrastructure system. Highlights: A multi-objective framework for structural retrofitting to increase the seismic resilience of existing RC buildings. The proposed framework selects the retrofit strategies optimized for seismic resilience index and cost of retrofit. Several retrofit strategies including different jacketing materials of various thicknesses and retrofit plans are selected. Three seismic intensity levels are taken into account. The optimal set of solutions is calculated through the non-dominated sorting genetic algorithm II.